HIV-Infected Mothers Who Decide to Breastfeed Their Infants Under Close Supervision in Belgium: About Two Cases - Bansaccal, Nordin; Van der Linden, Dimitri; Marot, Jean-Christophe; Belkhir, Leïla (Frontiers in Pediatrics, 2020)
Introduction: In most industrialized countries, human immunodeficiency virus (HIV) infection remains a formal contraindication to breastfeeding. However, for the past 9 years, the World Health Organization (WHO) has recommended, for developing countries, that mothers infected with HIV and treated by combined antiretroviral therapy (cART) should breastfeed their infants. HIV-infected women coming from developing countries and living in industrialized settings are increasingly expressing their natural desire to breastfeed. To avoid uncontrolled breastfeeding practices and reduce the risk of mother-to-child transmission of the virus, there is an urgent need to consider the wishes of these women. Discussion: We report two cases in which specific guidelines were implemented in order to support the mothers’ choice to breastfeed in Belgium. As a result of different prophylactic measures including antiretrovirals in mothers and infants and close follow-up, none of the infants were infected. Conclusions: National or international recommendations for HIV-infected mothers who choose to breastfeed in industrialized countries remain unclear and discordant. There is an unmet need for experts to address this emerging issue and to develop an international consensus for the monitoring and prophylactic management of exposed-infants.